Learning with the Augmented Reality EduPARK Game-Like App: Its Usability and Educational Value for Primary Education - Pombo, Lúcia (2020)
The EduPARK is a research and development project that intends to promote interdisciplinary mobile learning, supported by the development of an application to be used in an urban park, providing students’ involvement, motivation and engagement to enhance authentic and contextualized learning. The EduPARK project follows a qualitative interpretative methodology fitting in a design-based research, a useful framework for developing technology-enhanced learning resources comprising various cycles of prototype refinement: a game-like app for mobile devices, with Augmented Reality (AR) contents that follows geocaching principles. After those refinement stages, the final version of the app was released for the public in the Google Play Store; and around 50 activities were organized to collect systematic data to better understand mobile learning in outdoor settings, not only in formal but also in non- and informal contexts. To date, EduPARK has involved about 800 students from primary to higher education, 200 teachers and 60 tourists; however, this paper reports a survey study focused particularly on data of participants attending the first four years of primary education. A total of 290 students, organized in 73 teams, completed the game and expressed their opinion about the usability and the educational value of the app in a questionnaire applied after the activity; and automatic app loggings were collected. Results show that the EduPARK app achieved a good usability and has educational value for primary education students. The present work proposes a data collection tool, inspired in Brooke’s instrument, regarding the educational value of a game-based mobile AR resource.